2018
DOI: 10.1111/tan.13327
|View full text |Cite
|
Sign up to set email alerts
|

Activating killer‐cell immunoglobulin‐like receptor haplotype influences clinical outcome following HLA‐matched sibling haematopoietic stem cell transplantation

Abstract: Natural killer cells are thought to influence the outcome of hematopoietic stem cell transplant (HSCT), impacting on relapse, overall survival, graft versus host disease and the control of infection, in part through the complex interplay between the large and genetically diverse killer immunoglobulin-like receptor (KIR) family and their ligands. This study examined the relationship between KIR gene content and clinical outcomes including the control of opportunistic infections such as cytomegalovirus in the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…Cooley et al observed that patients with AML with KIR-B/x donors experienced a 30% improvement in RFS compared with those with A/A donors ( 40 ). Subsequently, many further investigations confirmed this beneficial effect of the KIR-B haplotype on relapse and survival in patients with hematological malignancies ( 50 , 51 , 57 , 67 , 72 , 76 , 79 , 81 , 85 , 88 92 , 96 , 98 , 101 104 ). Five of these studies reported that the protection effects mainly existed in the KIR Cen-B locus ( 67 , 88 , 91 , 92 , 96 ).…”
Section: Kir and Transplant Outcomesmentioning
confidence: 84%
See 4 more Smart Citations
“…Cooley et al observed that patients with AML with KIR-B/x donors experienced a 30% improvement in RFS compared with those with A/A donors ( 40 ). Subsequently, many further investigations confirmed this beneficial effect of the KIR-B haplotype on relapse and survival in patients with hematological malignancies ( 50 , 51 , 57 , 67 , 72 , 76 , 79 , 81 , 85 , 88 92 , 96 , 98 , 101 104 ). Five of these studies reported that the protection effects mainly existed in the KIR Cen-B locus ( 67 , 88 , 91 , 92 , 96 ).…”
Section: Kir and Transplant Outcomesmentioning
confidence: 84%
“…Regarding specific genotypes, some studies have reported that KIR haplotype B donors afforded a significantly reduced risk of GVHD ( 60 , 63 , 86 , 96 ). Consistent with these findings, Sivori et al suggested that donor NK cells expressing KIR2DS1 were efficient in killing allogenic dendric cells in the setting of haplo-HSCT, thus leading to a better GVHD control ( 136 ).…”
Section: Kir and Transplant Outcomesmentioning
confidence: 99%
See 3 more Smart Citations